Mobile phone addiction and achievement motivation in Chinese medical students: the chain mediating effect of anxiety and depression symptoms - Bai, Haoge; Wang, Yiju; Jin, Yan; Zhang, Zongyao; Wang, Juan; Meng, Yang; Sun, Hao; Xie, Hui (Frontiers in Psychology, 2025)
IntroductionMobile phone addiction (MPA) is an escalating issue, particularly among high-pressure medical students prone to over-reliance on mobile phones, and it is closely associated with lower achievement motivation. This study aimed to explore the associations between Chinese medical students' achievement motivation, anxiety, depression, and MPA.MethodsSingle-site cluster sampling was used to recruit 2,977 undergraduate medical students (Years 1–3) from a large medical university in Shandong Province. Data were collected via the Achievement Motivation Scale (AMS), Generalized Anxiety Disorder Scale-7 (GAD-7), Patient Health Questionnaire-9 (PHQ-9), and Mobile Phone Addiction Index (MPAI), with 2,679 valid questionnaires retained.ResultsOf the participants, 26.58% had MPA, with an average MPAI score of 42.97 ± 12.12. The average AMS score was 1.87 ± 0.35. Multiple linear regression showed that gender, liking one's major, MPAI, 7, and PHQ-9 scores significantly influenced achievement motivation (all p < 0.05). Mediation analysis indicated that anxiety and depression played a chain mediating role in the relationship between MPA achievement motivation: the total indirect effect was −0.114 (95%CI = [−0.133, −0.095]), including three paths: MPAI → GAD7 → AMS (effect = −0.027, 95%CI = [−0.047, −0.008]), MPAI → PHQ9 → AMS (effect = 95%CI = [−0.042, −0.023]), and MPAI → GAD7 → PHQ9 → AMS (effect = −0.055, 95% CI = [−0.070, −0.041]).DiscussionMPA correlates with lower achievement motivation in Chinese medical students, with anxiety and depression acting as mediators. Universities should take targeted measures to address MPA, in anxiety and depression, and improve medical students' achievement motivation.